Hydroxychloroquine-induced hyperpigmentation in a 14-year-old female with systemic lupus erythematosus - Alexander KC Leung; Tara McMillan; Andrea Human; Joseph M Lam (BioExcel Publishing Ltd, 2020)
Hydroxychloroquine (HCQ)-induced hyperpigmentation is uncommon but is increasingly recognized. To our knowledge, HCQ-induced hyperpigmentation has not been reported in the pediatric age group. Herein, we present the case of a 14-year-old girl with systemic lupus erythematosus, who developed hyperpigmentation on her shins and dorsum of the left foot, approximately 3 years after initiating treatment with HCQ. Physicians who treat children with HCQ for reasons such as rheumatologic disorders, dermatologic disorders and, more recently, coronavirus disease-19 should be aware of this less-known side effect of HCQ.